Water in Bucharest : A Utility’s Efficiency Gains under a Concession - World Bank (Washington, DC, 2012)
In March 2000 Bucharest entered into a concession contract for its water utility with the aim of turning around the utility's faltering performance. Under the private operator the utility has raised service quality above Romanian standards and toward Western European levels. By 2008 efficiency gains had produced cost savings totaling US$349 million. The concessionaire has financed US$259 million in investment, without public subsidy, while keeping tariffs well below the Romanian average. Not all water concessions have been as successful. What accounts for the gains under this one? The concession of Bucharest's water utility has brought its citizens higher-quality water services, at a lower cost, than they could have had under continued municipal provision. The credit for this goes to the leadership of the municipality and the municipal utility in the late 1990s, which saw that private finance and management were needed to reverse the cycle of poor performance.